105 Differences in myocardial mechanics between ischaemic and non-ischaemic cardiomyopathy assessed by cmr: a sub-group analysis of the vindicate trial. (5th June 2017) - Foley, James RJ; Swoboda, Peter P; Fent, Graham J; Garg, Pankaj; Ripley, David P; McDiarmid, Adam K; Dobson, Laura E; Musa, Tarique A; Plein, Sven; Witte, Klaus K; Greenwood, John P
Abstract : Background: Prognosis and treatment of patients with chronic heart failure (CHF) differs according to whether it is ischaemic (ICM) or non-ischaemic cardiomyopathy (NICM). Multi-parametric cardiovascular magnetic resonance (CMR) can distinguish these aetiologies; strain imaging however may confer incremental diagnostic and prognostic information over left ventricular ejection fraction (LVEF). We hypothesised in a prospectively recruited sample of CHF patients, ICM and NICM have different myocardial strain patterns. Methods: The VINDICATE trial investigated efficacy of high dose vitamin D in patients with CHF. A subgroup of the trial underwent CMR, blood and cardiopulmonary exercise tests at baseline. 53 patients (31 ICM, 22 NICM) underwent identical 3.0T CMR protocols (Achieva, Philips Healthcare, Best, The Netherlands). Tissue tagging by spatial modulation of magnetization (SPAMM) (spatial resolution 1.51 × 1.57×10mm 3, tag separation 7 mm, 18 phases, typical TR/TE 5.8/3.5 ms, flip angle 10°, typical temporal resolution 55 ms) was acquired in short axis slices acquired at the apex, mid-ventricle, and base. Late gadolinium enhancement (LGE) was performed 15 min following administration of 0.15 mmol/kg gadolinium DTPA. CMR data were analysed quantitatively using commercially available software (CVI42, Circle Cardiovascular Imaging Inc. Calgary, Canada and inTag v1.0, CREATIS lab, Lyon, France). Endocardial and epicardial contours were drawn on SPAMM sequences using a semi-automated process. Peak circumferential LV strain (Ecc ) was measured at apex, mid-ventricle, and base. LV twist was calculated by subtracting basal from apical rotation. Torsion was determined by: Torsion = Peak Twist x (Apical Radius+Basal Radius)/2xApex to Base length Results: The two groups were comparable for baseline demographics (Table 1). The ICM group had significantly more prior revascularisation (CABG/PCI). There was no significant difference between the 2 groups in both LV dimensions and LVEF, however ICM had significantly more LGE (Table 2). There was no significant difference between the 2 groups in Ecc . NICM patients had significantly lower LV twist and torsion compared to the ICM group 6.0±3.68° vs 8.8±4.32° p=0.020 and 6.3±3.79° vs 8.8±4.69° p=0.048 respectively. Conclusion: Despite similar EF and Ecc, patients with NICM had significantly less LV torsion than ICM. Myocyte dysfunction in ICM is more sub-endocardial due to the wave-front of ischaemia and more global in NICM. Relative perseveration of LV torsion of ICM over NICM is likely a result of sparing of sub-epicardial fibres and an increased compensatory recruitment of sub-epicardial fibres that are predominantly responsible for LV torsion. Recognition of different torsion patterns of ICM and NICM gives insight into aetiology of CHF, which may assist patient diagnosis and management, especially in those unable to have contrast agents.